2018
DOI: 10.1016/j.jpeds.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Infants with Atypical Presentations of Alveolar Capillary Dysplasia with Misalignment of the Pulmonary Veins Who Underwent Bilateral Lung Transplantation

Abstract: The 1- and 5-year survival rates for infants with atypical ACDMPV are similar to infants transplanted for other indications. Given the clinical and histopathologic spectra, ACDMPV should be considered in infants with hypoxemia and pulmonary hypertension, even beyond the newborn period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 32 publications
(65 reference statements)
2
60
0
3
Order By: Relevance
“…The histological findings diagnostic for ACD/MPV are characterized by decreased pulmonary capillaries, thickened alveolar septa, medial hypertrophy of small pulmonary arteries, and malposition of pulmonary veins adjacent to small pulmonary arteries, which clinically results in lethal pulmonary hypertension and hypoxemia . Towe et al recently reported a case series study in which six infants underwent bilateral lung transplantation for ACD/MPV, and the posttransplant outcomes were comparable to those of infants transplanted for other indications …”
Section: Introductionmentioning
confidence: 99%
“…The histological findings diagnostic for ACD/MPV are characterized by decreased pulmonary capillaries, thickened alveolar septa, medial hypertrophy of small pulmonary arteries, and malposition of pulmonary veins adjacent to small pulmonary arteries, which clinically results in lethal pulmonary hypertension and hypoxemia . Towe et al recently reported a case series study in which six infants underwent bilateral lung transplantation for ACD/MPV, and the posttransplant outcomes were comparable to those of infants transplanted for other indications …”
Section: Introductionmentioning
confidence: 99%
“…This could allow neonatologists to give a diagnosis rapidly but this examination is often impossible because of patients’ haemodynamic instability. Moreover, like suggested in literature, a negative result for biopsy could be an issue of sampling bias, suggesting patchy lung involvement, mostly in patients with atypical presentations 10 11. Therefore, a normal lung biopsy should not eliminate ACD.…”
Section: Discussionmentioning
confidence: 86%
“…The age of death is also variable: two of our cases presented with prolonged survival, 3.3 months and 1 year and 2 months, respectively. Some cases with a prolonged survival were described in the literature 7 10 11. The longest survival was described by Reiter et al in 2016 about a 3-year-old patient, still alive at the time of publication 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ACDMPV can present with persistent pulmonary hypertension in the neonatal period and may have death early in life (Bishop et al, ). However, some patients may have atypical presentations with later onset of symptoms and milder symptoms, as summarized by (Towe et al, ). Ito et al () published a case with ACDMPV and FOXF1 frameshift mutation that presented late and survived to over 3 years of age.…”
Section: Introductionmentioning
confidence: 99%